The Influence of Principal's Academic Supervision on Teachers’ Professionalism Teaching Motivation as a Mediator for Kindergarten Teachers - Isriyati Isriyati; Tri Suminar; Ali Formen (Universitas Negeri Semarang, 2024)
The success of a school in achieving its learning program objectives is largely determined by its principals’ leadership styles. School principals are expected to conduct academic supervision of the teachers in their institutions. Academic supervision is a series of activities to help teachers develop their ability to manage the learning process to achieve learning objectives. Motivation is an encouragement in a person to make changes in behavior, in this case the expected behavior is teacher professionalism. Based on his approach is ex-post facto research. The purpose of this study is to analyze the influence of academic supervision on teacher professionalism through teaching motivation. The results of the study that Academic Supervision Mediates Teacher Professionalism both directly and indirectly. Recommendations for school principals to carry out academic supervision in a structured manner.